The Edinburgh companion to children's literature - Beauvais, Clémentine; Nikolajeva, Maria (Edinburgh University Press, 2017)
This collection takes informed and scholarly readers to the utmost frontier of children's literature criticism, from the intricate worlds of children's poetry, picturebooks and video games to the new theoretical constellations of critical plant studies, non-fiction studies and big data analyses of literature.